(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Foreign Direct Investment (FDI has been considered as a powerful weapon of globalization with double edge that cuts both ways mean it impacts positively and negatively. Its impacts positively by supporting the host country’s economy in terms of capital inflows and up-to date technology but FDI also affect the host country by overexploiting its resources. Despite all these thing, this capital provides an opportunity to underdeveloped and developing countries by providing to access new markets, advance technology, cost effective production facilities and more investment opportunities. It is a two way mechanism for both the countries first, from where FDI comes and second where FDI is invested in form Greenfield and Brownfield. For the host country, it is a new way to economic development. This chapter has been investigated the effect of FDI on economic growth of host country and effect of economic growth on FDI by applying regression analysis and found that that the overall model is positive and significant at 5 percent significance level for seven countries namely Afghanistan, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. However, for Bangladesh the model is found to be insignificant, at second stage, ADF test is employed to data for Stationarity check. ADF calculations indicate that both the variables are stationary at level and first difference at 1 percent level of significance; however few exceptions are there, at the final stage.